The relationship between mathematics self-efficacy and achievement in mathematics (2009)
This study examined the relationship between Mathematics Self-Efficacy and achievement in Mathematics. Three hundred and fifty-two (352) Senior Secondary 2 students in Oyo State were used for the study. Three hypotheses were used. The results show no significant difference between male and female achievement in Mathematics. Also, no significant difference was also obtained between male and female Mathematics Self-Efficacy and Mathematics achievement. The paper recommend that teacher should find ways of enhancing Mathematics Self- Efficacy in student and should place emphasis on student’s confidence to succeed in Mathematics achievement.